Analisis Yuridis Wanprestasi Dalam Perjanjian Pinjam Meminjam Uang : (Studi Putusan Nomor 10/Pdt.G.S/2019/PN.Smr) - Rani Lestari; Shinta Andriyani (Fakultas Hukum Universitas Mataram, 2023)
This research has the purpose to find out the default contract regulation in the loan agreement based on Indonesia's positive law, and find out the judge’s legal consideration when given the decision in the case court Number 10/PDT.G.S/2019/PN.SMR. The research method of this research is normative legal research which uses the conceptual approach, the statute approach, and the case approach, this research uses qualitative analysis. The result of this study showed that the default in contract regulation especially in the loan agreement has regulated in Article 1313 Indonesia Civil Code about the contract, Article 1754 Indonesia Civil Code about loan agreement, and especially Article 1265 Indonesia Civil Code about null and void the agreement. Furthermore, the judge’s legal consideration when deciding the case in the court decision Number 10/PDT.G.S/2019/PN.SMR stated the defendant has default in contract based on the claim in the court, and the evidence in the court process such as a statement letter on July 26, 2019. This is a new deal or agreement between the plaintiff with the defendant which exists as the principle of consensually vide (Article 1320 Indonesia Civil Code), this agreement is like legislation for the parties (article 1338 Indonesia civil Code). This is a type of novation/ restructuring that regulated in Article 1413 paragraph 1 Indonesia Civil Code. Because of this, the agreement on this case is the letter of statement on 26 July 2019.